A phase-field model for the evaporation of thin film mixtures - Ronsin, Olivier; Jang, Dongju; Egelhaaf, Hans-Joachim; Brabec, Christoph; Harting, Jens (Physical Chemistry Chemical Physics, 2020)

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, Dongju; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Fully printed flexible perovskite solar modules with improved energy alignment by tin oxide surface modification - Dong, Lirong; Qiu, Shudi; García Cerrillo, José; Wagner, Michael; Kasian, Olga; Feroze, Sarmad; Jang, Dongju; Li, Chaohui; Le Corre, Vincent Marc; Zhang, Kaicheng; Peisert, Heiko; U. Kosasih, Felix; et al. (Energy and Environmental Science, 2024)
Fully printed flexible perovskite solar cells (f-PSCs) show great potential for the commercialization of perovskite photovoltaics owing to their compatibility with high-throughput roll-to-roll (R2R) production. However, the challenge remains in the deficiency in controlling interfacial recombination losses of the functional layer, causing remarkable loss of power conversion efficiency (PCE) in industrial production. Here, a fullerene-substituted alkylphosphonic acid dipole layer is introduced between the R2R-printed tin oxide electron transport layer and the perovskite active layer to reduce the energetic barrier and to suppress surface recombination at the buried interface. The resulting f-PSCs exhibit a PCE of 17.0% with negligible hysteresis, retain 95% of their initial PCE over 3000 bending cycles and achieve a T95 lifetime of 1200 h under 1 sun and 65 °C in nitrogen atmosphere. Moreover, the fully printed flexible perovskite solar mini-modules (f-PSMs) with a 20.25 cm2 aperture area achieve a PCE of 11.6%. The encapsulated f-PSMs retain 90% of their initial PCE after 500 h damp-heat testing at 65 °C and 85% relative humidity (ISOS-D3). This work marks an important progress toward the realization of efficient and stable flexible perovskite photovoltaics for commercialization.
CRIS-Team Scopus Importer:2024-08-16

Fully Solution Processed Pure α-Phase Formamidinium Lead Iodide Perovskite Solar Cells for Scalable Production in Ambient Condition - Yang, Fu; Dong, Lirong; Jang, Dongju; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Guo, Fei; Li, Cong; Arrive, Charline; Bertrand, Mélanie; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2020)
Manufacturing commercially viable perovskite solar cells still requires appropriate low-temperature and scalable deposition processes to be developed. While α-phase FAPbI3 has higher thermal stability and broader absorption than MAPbI3, there still is no report of a pure α-phase FAPbI3 perovskite film obtained by a scalable printing method. Moreover, spontaneous conversion of the α-phase to non-perovskite δ-phase under ambient conditions poses a serious challenge for practical applications. Herein, a scalable and fully solution based printing method for the fabrication of pure α-phase FAPbI3 perovskite solar cells is reported. Through adding N-methyl pyrrolidone and methylammonium chloride to the dimethylformamide based precursor solution to control the crystallization, and vacuum or air-flow assisted film drying, pure α-FAPbI3 phase is obtained by doctor blading. The resulting α-FAPbI3 film is highly stable, with no δ-FAPbI3 phase being formed even after keeping it in an ambient atmosphere over a period of 200 days without encapsulation. In addition, a fully solution processed PSC with a PCE of 16.1% is processed by the vacuum assisted method, and 17.8% by the air-flow assisted method. Replacing silver with a printed carbon electrode provides a stable PCE up to 15% for the vacuum assisted and 16.4% for the air-flow assisted method, which is the highest performance of FAPbI3 solar cells to date. Compared with MAPbI3, the fully printed FAPbI3 perovskite devices exhibit a remarkable thermal stability in humid atmospheres which makes them a promising candidate for scalable production and commercialization.
CRIS-Team Scopus Importer:2020-10-02
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; α-FAPbI

In Situ Probing the Crystallization Kinetics in Gas-Quenching-Assisted Coating of Perovskite Films - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Jang, Dongju; Le Corre, Vincent Marc; García Cerrillo, José; Ronsin, Olivier J.J.; Yang, Fu; Guo, Fei; Zhang, Kaicheng; Lüer, Larry; Harting, Jens; et al. (Advanced Energy Materials, 2024)
The pursuit of commercializing perovskite photovoltaics is driving the development of various scalable perovskite crystallization techniques. Among them, gas quenching is a promising crystallization approach for high-throughput deposition of perovskite films. However, the perovskite films prepared by gas-quenching assisted blade coating are susceptible to the formation of pinholes and frequently show inferior crystallinity if the interplay between film coating, film drying, and crystallization kinetics is not fully optimized. That arguably requires a thorough understanding of how single processing steps influence the crystallization kinetics of printed perovskite films. Here, in situ optical spectroscopies are integrated into a doctor-blading setup that allows to real-time monitor film formation during the gas-quenching process. It is found that the essential role of gas quenching treatment is in achieving a smooth and compact perovskite film by controlling the nucleation rate. Moreover, with the assistance of phase-field simulations, the role of excessive methylammonium iodide is revealed to increase grain size by accelerating the crystal growth rate. These results show a tailored control of crystal growth rate is critical to achieving optimal film quality, leading to fully printed solar cells with a champion power conversion efficiency of 19.50% and mini solar modules with 15.28% efficiency are achieved.
CRIS-Team Scopus Importer:2024-01-12
Keywords: blade coating; fully printed perovskite photovoltaics; gas quenching; in situ techniques; phase-field simulations

Low Temperature Processed Fully Printed Efficient Planar Structure Carbon Electrode Perovskite Solar Cells and Modules - Yang, Fu; Dong, Lirong; Jang, Dongju; Saparov, Begench; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
Scalable deposition processes at low temperature are urgently needed for the commercialization of perovskite solar cells (PSCs) as they can decrease the energy payback time of PSCs technology. In this work, a processing protocol is presented for highly efficient and stable planar n–i–p structure PSCs with carbon as the top electrode (carbon-PSCs) fully printed at fairly low temperature by using cheap materials under ambient conditions, thus meeting the requirements for scalable production on an industrial level. High-quality perovskite layers are achieved by using a combinatorial engineering concept, including solvent engineering, additive engineering, and processing engineering. The optimized carbon-PSCs with all layers including electron transport layer, perovskite, hole transport layer, and carbon electrode which are printed under ambient conditions show efficiencies exceeding 18% with enhanced stability, retaining 100% of their initial efficiency after 5000 h in a humid atmosphere. Finally, large-area perovskite modules are successfully obtained and outstanding performance is shown with an efficiency of 15.3% by optimizing the femtosecond laser parameters for the P2 line patterning. These results represent important progress toward fully printed planar carbon electrode perovskite devices as a promising approach for the scaling up and worldwide application of PSCs.
CRIS-Team Scopus Importer:2021-06-18
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; perovskite solar cells

Precursor-Engineered Volatile Inks Enable Reliable Blade-Coating of Cesium–Formamidinium Perovskites Toward Fully Printed Solar Modules - Du, Tian; Rehm, Viktor; Qiu, Shudi; Pal, Subhajit; Jang, Dongju; Peng, Zijian; Zhang, Jiyun; Yuan, Haozhen; Briscoe, Joe; Heiß, Wolfgang; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Science, 2024)
Reliable fabrication of large-area perovskite films with antisolvent-free printing techniques requires high-volatility solvents, such as 2-methoxyethanol (2ME), to formulate precursor inks. However, the fabrication of high-quality cesium–formamidinium (Cs–FA) perovskites has been hampered using volatile solvents due to their poor coordination with the perovskite precursors. Here, this issue is resolved by re-formulating a 2ME-based Cs0.05FA0.95PbI3 ink using pre-synthesized single crystals as the precursor instead of the conventional mixture of raw powders. The key to obtaining high-quality Cs–FA films lies in the removal of colloidal particles from the ink and hence the suppression of colloid-induced heterogeneous nucleation, which kinetically facilitates the growth of as-formed crystals toward larger grains and improved film crystallinity. Employing the precursor-engineered volatile ink in the vacuum-free, fully printing processing of solar cells (with carbon electrode), a power conversion efficiency (PCE) of 19.3%, a T80 (80% of initial PCE) of 1000 h in ISOS-L-2I (85 °C/1 Sun) aging test and a substantially reduced bill of materials are obtained. The reliable coating methodology ultimately enables the fabrication of carbon-electrode mini solar modules with a stabilized PCE of 16.2% (average 15.6%) representing the record value among the fully printed counterparts and a key milestone toward meeting the objectives for a scalable photovoltaic technology.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cesium formamidinium perovskite; reliable blade coating; single crystals; solar module; volatile ink

Printing High-Quality Formanidinum Lead Triiodide Films: Understanding the Critical Role of α-Phase Nucleation Before Thermal Annealing - Qiu, Shudi; Dong, Lirong; Jang, Dongju; Yang, Fu; García Cerrillo, José; Li, Chaohui; Xie, Zhiqiang; Luo, Junsheng; Guo, Fei; Distler, Andreas; Du, Tian; Brabec, Christoph; et al. (Advanced Energy Materials, 2024)
Upscaling the coating of formamidinium lead triiodide (FAPbI3) thin film is essential to realizing full printing and thereby roll-to-roll production of perovskite photovoltaics. However, thin-film FAPbI3 processed from antisolvent-free, printing methods suffer from undesirable degradation to the non-photoactive phase, particularly in ambient processing conditions. Here, the most critical stage in thin-film processing is identified as the gas-quenching treatment of the as-cast wet film. It is crucial to achieve both the nucleation of α-phase nanocrystals and their sufficient growth at room temperature, which are indispensable for templating the growth of a highly crystalline and stable α-FAPbI3 film during subsequent thermal annealing. The gas-quenching-treated film without these α-phase nanocrystals can only be converted to meta-stable α-FAPbI3 by thermal annealing. By precisely identifying the spontaneous doping of cesium ion (Cs+) as a key factor in triggering α-FAPbI3 nucleation and the role of chloride ion (Cl−) in enhancing nanocrystal growth, a generalized mechanism for additive engineering for the precursor ink is theorized. The identified mechanism translates to a power conversion efficiency of 19.36% for fully printed carbon-electrode solar cells, 16.23% for carbon-electrode minimodules, and excellent operational stability, showing the promising potential of this proposed fabrication route in the upscaling of perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: carbon-electrode; cesium ion; FAPbI; nucleation; perovskite photovoltaics

Roll-to-Roll Deposition of Wide-Bandgap CsFAPbBr3 Perovskite Solar Cells in Ambient Air with Optimized Ink Formulation - Jafarzadeh, Farshad; Dong, Lirong; Jang, Dongju; Wagner, Michael; Koch, Giulio; Qiu, Shudi; Feroze, Sarmad; García Cerrillo, José; Brabec, Christoph; Di Carlo, Aldo; Brunetti, Francesca; Egelhaaf, Hans-Joachim; et al. (Solar RRL, 2024)
The growing demand for sustainable energy solutions has made the development of scalable, efficient, and cost-effective perovskite solar cells (PSCs) increasingly important. Wide-bandgap perovskites (WB-PSCs) stand out due to their efficiency in low-light conditions and their use in tandem solar cells. WB-PSCs are currently behind conventional PSCs in upscaling, with limited success in printing wide bandgap PSCs. Developing upscaling methods is essential to fully realize their potential in the renewable energy sector. This research addresses the development of roll-to-roll (R2R) slot-die coating of Cs0.05FA0.95PbBr3-based WB-PSCs by focusing on improving the film formation process and ink formulation. By adding optimal concentration of CsBr and performing in situ characterization, we obtained Cs0.05FA0.95PbBr3 films with enhanced morphology and crystallinity in ambient conditions (50% RH), without inducing secondary phase formation. In addition, slot-die coating defects are eliminated through introducing DMSO: Butanol (9:1) solvent system. The R2R coated wide-bandgap PSCs reaches a power conversion efficiency (PCE) of up to 8.97% under 1-sun conditions and 18.3% PCE under indoor conditions. The corresponding R2R coated modules with a 5 × 5 cm2 active area achieve a PCE of 5.8%, representing a crucial step towards the high-throughput, cost-effective production of perovskite solar modules.
CRIS-Team Scopus Importer:2024-10-11
Keywords: ambient deposition; ink formulation; roll-to-roll; slot-die coating; wide-bandgap perovskite solar cells

Simplifying contact-layer design for high-throughput printing of flexible perovskite photovoltaics - Dong, Lirong; Qiu, Shudi; Feroze, Sarmad; Wagner, Michael; Kasian, Olga; Peisert, Heiko; Kosasih, Felix U.; Ducati, Caterina; García Cerrillo, José; Tian, Jingjing; Li, Chaohui; Jang, Dongju; et al. (Energy and Environmental Science, 2024)
The realization of scalable roll-to-roll production processes for metal-halide perovskite modules is a necessary development for transferring developments and technologies from the lab to the fab. Before that, it is imperative to close the efficiency gap not only between the devices fabricated on rigid substrates versus flexible substrates, but also between solar cells to solar modules. In this regard, a critical assessment of device architectures that are more compatible to scalable fabrication is needed. Obviously, the adaption to mass manufacturing must not negatively impact device performance and operational stability. Here, by investigating the properties of printed fullerene-based phosphonic acid dipole interface layers, we establish simplified self-assembled monolayer (SAM) based n-i-p architectures without any charge extraction layers other than SAMs, which are easily processed and are thus ideally suited for mass production. We show that a contact-layer design with a printed fullerene-based SAM that has phosphonic acid is sufficient to provide good charge selectivity and to minimize interface recombination at the bottom electrode. We further show that the same SAM molecule can be used as a p-type interface material on top of the perovskite. This simplified contact-layer design, which is based on one material for both hole and electron work-function adaption is successfully integrated into our fully printed module process comprising the deposition of a carbon top electrode. The achieved open-circuit voltage exceeds 1.1 V, and the fill factor surpasses 70%, highlighting the potential of this novel interface design concept for both rigid and flexible substrates.
CRIS-Team Scopus Importer:2024-09-06

Upscaling of Perovskite Photovoltaics - Jang, Dongju; Yang, Fu; Dong, Lirong; Brabec, Christoph; Egelhaaf, Hans-Joachim (wiley, 2021)
Hybrid organic-inorganic perovskite solar cells have reached a certified efficiency of over 25% during the past decade, which has attracted significant attention as a promising candidate for photovoltaics (PVs) applications. However, the most efficient perovskite solar cells were performed by the spin coating technique, which is extremely limited in commercialization. Besides, the efficiencies of large-area perovskite cells and modules are still significantly lower. There are still some challenges that need to overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The most important challenge is how to prepare high-quality perovskite layers using cheaper and scalable techniques with high reproducibility. On the other hand, select and deposit charge extraction/transport layers, and the bottom and top electrodes using cheaper and scalable techniques are also important. In this review, recent progress and challenges of the scalable technologies for solution-based coating and printing methods are summarized and analyzed based on the current progress in scalable technologies for solution-based preparation of large-area perovskite PVs. Based on our analysis, we try to point out the major challenges to overcome to successfully bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. Finally, strategies and opportunities are proposed to promote stable and efficient large-area perovskite PVs toward commercialization.
CRIS-Team Scopus Importer:2024-12-16
Keywords: module; perovskite solar cells; roll-to-roll production; upscaling

Upscaling Solution-Processed Perovskite Photovoltaics - Yang, Fu; Jang, Dongju; Dong, Lirong; Qiu, Shudi; Distler, Andreas; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
The performance of hybrid organic–inorganic perovskite solar cells has reached a certified efficiency of 25.5% over the past decade, which has attracted significant attention as a promising candidate for photovoltaic (PV) applications. However, the most efficient perovskite solar cells were produced by the technique of spin coating, which is extremely limited in terms of upscaling production for the commercialization of the technology. Furthermore, the efficiencies of large-area perovskite modules are still significantly lower than those of lab size solar cells. Thus, there are still some challenges that need to be overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The first challenge lies in preparing high-quality perovskite layers by low-cost and scalable techniques with high reproducibility. Second, selecting and depositing charge extraction layers as well as bottom and top electrodes by scalable and low-cost techniques are essential tasks. In this review, recent progress and challenges of scalable technologies for solution-based coating and printing of perovskite PVs are summarized and analyzed. Based on the analysis, strategies and opportunities are proposed to promote the development of stable and efficient large-area perovskite PV toward commercialization.
CRIS-Team Scopus Importer:2021-10-22
Keywords: high-efficiency; long-term stability; perovskite photovoltaics; roll-to-roll production; scalable coating